VALIDATION OF METHOD FOR YERSINIA ENTEROCOLITICA ISOLATION FROM RAW MATERIALS OF ANIMAL ORIGIN - I. V. Borodkina; N. B. Shadrova; O. V. Pruntova; S. I. Danilchenko (Ветеринария сегодня)
Upward trend in the number of human yersiniosis cases, caused by bacterium Yersinia enterocolitica, is globally observed nowadays. This microorganism is widely spread in the environment, able to persist for prolonged periods in animal products and propagate under low temperatures. Basic infection sources are meat and meat products. In order to isolate Yersinia enterocolitica from food and feed samples horizontal method for the detection pursuant to GOST ISO 10273-2013 was used. It was noted, that Yersinia enterocolitica isolation is associated with certain difficulties, because the sample contains only small quantities of the agent and only the use of special techniques allows removing the concurrent microflora. It was proposed to use cold enrichment (4 ± 1) °C of the test material before conventional technique is started. The technique was validated pursuant to GOST ISO 16140-2011. As a result, it was established that validated method for Yersinia enterocolitica bacteria detection in food products, performed at the Microbiology Laboratory, is specific. The method sensitivity is 10 CFU/cm3. Intralaboratory reproducibility and repeatability were confirmed by relevant tests. Additional culture step at (4 ± 1) °C allows complete inhibition of non-psychrophilic microorganisms’ growth.